Cambridge preliminary English test 3 with ansers: Examination papers from university of Cambridge ESOL examinations English for speaker of other language - Cambridge University (Cambridge University, 2013)
Đưa ra các lưu ý đối với học viên về kỳ thi Pet. Cung cấp 4 bài kiểm tra đề thi PET, bao gồm: Nghe, Nói, Đọc, Viết. Kèm theo đáp án và tapescript.